Analysis of The Application of Lean Manufacturing with Methods Material Information Flow Chart (MIFC) and Fuzzy Failure Mode, Effects and Criticality Analysis (FMECA) - Mukti, Prasetyo; Islami, Mega Cattleya Prameswari Anissa (Manunggal Halim Jaya, 2025)
PT XYZ is a company specializing in the manufacturing of agricultural equipment. Currently, the company is facing issues related to waste in its production processes, which are negatively affecting product quality. PT XYZ aims to address these problems in order to enhance both productivity and profitability. To resolve these challenges, the company has adopted a structured approach, beginning with the development of a Material Information Flow Chart (MIFC), followed by an analysis using Failure Mode, Effects, and Criticality Analysis (FMECA) based on fuzzy logic. The results of the MIFC analysis show a reduction in lead time from 0.45 days under current conditions to 0.35 days under the improved scenario. This improvement is attributed to the implementation of an ERP system and the introduction of visual monitoring tools. Meanwhile, the FMECA fuzzy analysis identified the primary causes of disruptions that should be prioritized for corrective action. These include non-compliance with standard operating procedures (SOPs), high levels of mental stress among workers, the use of materials that do not meet specifications, and unfavorable environmental conditions.